Rod responses produce the peripheral flicker illusion - Meidi Niikawa; Hiroyuki Ito (i-Perception)
When a green/blue object is presented on a red background and viewed in peripheral vision, the object is seen to flash twice or to flicker (the peripheral flicker illusion). We showed that the ratio of photopic luminances of the object and the red background determines the optimal photopic luminance of the green/blue object required for the illusion to occur. The results were analyzed using scotopic luminance to investigate the role of rod responses. It was found that the scotopic luminance of the green/blue object should be higher than that of the red background for the illusion to occur. This suggests that the red background enhances the flickering impression of the object when there is a sudden increase in the rod responses.